Butcher, baker, candlestick taker [book club bag] - Meredith, Patricia (Meredith, Patricia. Spokane Clock Tower mysteries, 2021)
"Archie Prescot has traveled across the country to design the now-iconic Spokane clock tower for the new Great Northern Railroad Depot. When his talent for creating unique clock chimes connects him with a local patroness, he is thrilled, until she is discovered dead in the workshop of his new colleague. Her grand home on the South Hill provides ample suspects, as Archie works with his lodgers, Detective Carew and his twin brother, to prove his fellow inventor and himself innocent of the crime. While on the hunt for the murderer, romance crops up when a young lady crosses his path with a mysterious past of her own. Six intersecting storylines create a cohesive look at a convoluted murder that will require all points of view to discover the truth ..."--Amazon